Potential hydrometallurgical processes to recycle metals from discarded personal computer. Issue 3 (4th July 2022) - Dinkar, Om Shankar; Parween, Rukshana; Panda, Rekha; Choubey, Pankaj Kumar; Ambade, Balram; Jha, Manis Kumar
ABSTRACT: Rapid technological modernization has accelerated the replacement of older electronic goods with newer ones, which has led to the generation of huge quantities of discarded electronic items at its end-of-life, known as electronic wastes (e-wastes). The growing quantity of e-wastes has become a major threat to the society as well as environment. On the other hand, e-wastes contain several valuable metals and materials of high economic value, which compels researchers to work in the area for secondary resources for metal recovery. Metal recovery from such secondary resources will not only preserve the primary resources but also reduce the loss of valuable metals/materials, protect the environment from their hazardous effects as well as reduce the demand-supply gap of metals up to some extent. In view of the above, present study is focused on the possible effort to figure out variety of metals present in the component of waste personal computers (WPCs) as well as different recycling processes implemented for the efficient recovery of metals.